Wettability modification of glass surfaces by deposition of transparent conducting oxides using laser texturing - Abdul Fattah, Mohamad Tahir; Syarifah Nur Aqida, Syed Ahmad; Izwan, Ismail (Springer, 2025)
This research focuses on tuning the wettability of hydrophilic glass using a facile methodology, where the glass is coated with transparent conducting oxides (TCO). The use of eco-friendly TiO2 is proposed as a replacement for hazardous chemicals traditionally used as low-surface-energy agents for wettability transformation. Glass samples were laser textured at 84 kW/mm2, with variations in hatch patterns and spacings, following the Box-Behnken Design of experiments. The samples were characterized for surface wettability, surface energy, and surface topography. Significant reductions in surface energy and water adhesion were recorded for samples with a 0.2 mm hatch spacing, resulting in an increase in the water contact angle up to 61.23°, corresponding to a surface energy of 41.95 mJ/m2. To enhance the hydrophobic effect, the observed micropattern formation requires an Rz value greater than 121 µm whereas surface chemistry analysis showed that depletion of hydroxyl functional groups occurred in the modified glass, with a 65.2% reduction in SiO2 compared to pristine glass. From statistical analysis, the hatch spacing contributed up to 94.1% of the variation in water contact angle, followed by frequency (5.7%) and hatch pattern (0.2%). The modified glass surface demonstrated the ability to produce tunable wettability by altering its surface topography and surface chemistry using TCO.